2010
DOI: 10.1016/j.otsr.2010.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Fifth metacarpal neck fracture fixation: Locking plate versus K-wire?

Abstract: Level IV continuous prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 16 publications
5
105
1
11
Order By: Relevance
“…This finding is in line with those of previous studies regarding fracture reductions (assessed by apex dorsal angulation and shortening) achieved by antegrade intramedullary pinning and other surgical methods, such as percutaneous transverse pinning [19,20], miniplate [4,6], and percutaneous retrograde crossed pinning [16].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding is in line with those of previous studies regarding fracture reductions (assessed by apex dorsal angulation and shortening) achieved by antegrade intramedullary pinning and other surgical methods, such as percutaneous transverse pinning [19,20], miniplate [4,6], and percutaneous retrograde crossed pinning [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, Schädel-Höpfner et al [16], in a randomized study, compared the outcomes of antegrade intramedullary pinning and percutaneous retrograde crossed pinning for displaced fifth metacarpal neck fractures and found that antegrade intramedullary pinning produced better ROM, pain scores, and Steel scores (a score comprised of pain, ROM, grip strength, and radiographic deformity) in the fifth metacarpophalangeal joint after a mean patient followup of 17 months. Facca et al [4], in a randomized study, compared the outcomes of antegrade intramedullary pinning and the locking miniplate technique for treating patients with displaced fifth metacarpal neck fractures and also found antegrade intramedullary pinning produced significantly better ROM in the metacarpophalangeal joint after a mean followup of 4 months. Yammine and Harvey [21], in a meta-analysis, concluded that patients treated with antegrade intramedullary pinning showed better grip strength, fifth digit ROM, lower pain scores, and fewer complications than patients treated with percutaneous transverse pinning or miniplate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations